APPLICATION OF PERSON PROFILING METHODS IN PERSONAL MANAGEMENT - Madzuls, Juris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The present study explores the specificity and implementation of person profiling methods applied in personal management. Conducting serious negotiations and signing contracts, selecting personnel and carrying out internal investigations – all these processes force today's managers to use law enforcement methods. The method of person profiling is becoming an indispensable tool in economy, in processes of transactions and managing personnel, selecting personnel and determining their motivation.The main aim of the paper is to clarify and scientifically substantiate the necessity for the introduction of profiling as a method in personal management, secondly to determine the content of the person profiling method as a component of personnel management. In order to increase a degree of reliability of the results obtained by the applied profiling methods, the author performed an analysis and evaluation of documents, scientific, personnel management and psychological literature. Based on the analysis, conclusions on the need to implement the profiling method and the possibilities of staff evaluation will be summarized.The study was conducted in the State Border Guard using scientific, pedagogical and psychological literature analysis and evaluation and document analysis research method. The author brought the forward conclusion that profiling methodology allows to receive information that shows not only the organization management problems in the personnel management system, but also allows to make immediate, appropriate and adequate solutions to the management style adjustment, which will undoubtedly lead to the increased efficiency of staff and the whole organization.